Injury and training characteristics of male elite, development squad, and club triathletes - Vleck, V. E.; Garbutt, G. (International Journal of Sports Medicine, 1998)
Links between overuse injury prevalence in triathletes training for 1.5km, 40km, 10km triathlon and both intrinsic and extrinsic factors were assessed in 12 Elite, 17 Development and 87 male Club triathletes by a five year retrospective questionnaire. Elite, Development and Club triathletes differed in training mileage, duration and number of workouts but not in overall injury prevalence, distribution, and severity. Overuse injury occurred in 75.0% of male Elite Squad, 75.0% of Development Squad and 56.3% of Club athletes with 1.9-2.9 sites affected. The most common injuries - the achilles tendon (10.3-17.9%), lower back (15.8-17.9%) and knee (14.2-21.9% of injuries) - were also among the most severe. Running injuries accounted for more of the total number of injuries than cycling injuries in Elite (62.1 % vs 34.5%, p<0.05), Development (64.3% vs 25.0%, p<0.05) and Club triathletes (58.7% vs 15.9%, p<0.05). The number of running injuries sustained correlated with triathlon training distance, cycling distance (p<0.03), swimming distance (p<0.01), number of triathlon workouts (p<0.03) and number of running sessions (p<0.03) within one weeks race training. The number of overuse injuries sustained during cycling correlated with time spent running and cycling.